Image Simulation and Analysis - Sengebusch, Karsten (Optik & Photonik (Internet), 2018)
No image is perfect, except for paintings. We have to deal with various noise sources and image sensor artifacts as well as with diffraction and other geometrical effects. The simulation of such artifacts is a great help during a design process and a perfect method for proof of concepts: Without access to any real hardware it is possible to predict and visualize the performance of opto‐electronic systems. Algorithms for correction or analysis of image data can be developed and evaluated a long time before the imaging hardware is ready to use. The statistical methods used during the simulation process can also be used reversely to provide a deep statistical analysis of already existing images. Such an analysis as well as the comparison with simulated images can help to identify the source of artifacts and design mistakes or even be used during forensic work. Last but not least, the reverse usage of the simulation of diffraction and wave front propagation is a very effective method for the generation of computer generated holograms or DOEs.